Earnings Manipulation in Times of COVID-19: Evidence from European Union Countries - Jarne, José I.; Wroblewski, David; Callao, Susana (Comparative Economic Research. Central and Eastern Europe, 2025)
The coronavirus pandemic has caused the world’s worst crisis. No other situation in recent history has had such a negative impact on the global economy. Consequently, companies have been forced to adapt to the new circumstances and strive in this drastically changing world. The objective of this study is to analyze the impact of the COVID-19 pandemic on earnings management practices in the context of European Union countries. We applied accruals-based methodology, and to estimate discretionary part of accruals we used Dechow, Sloan, and Sweeney model. Our results confirm that companies reduced earnings management activities during COVID compared to pre-pandemic. This reduction is influenced by the economic situation of the country and companies, as well as by whether or not they are listed on the stock markets. In particular, we observed that the impact of COVID-19 on the change in manipulation is lower in countries with higher GDP, as well as in listed companies and those with negative results. Our findings have both theoretical and practical implications for the practices of earnings management in European Union countries in times of pandemic. We contribute to the literature by improving understanding of the quality of corporate financial reporting during the COVID-19 period, one of the most important crisis occurred in recent history.